2021
DOI: 10.3389/fchem.2021.786746
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexanohemicucurbit[8]uril Inclusion Complexes With Heterocycles and Selective Extraction of Sulfur Compounds From Water

Abstract: Solid-phase extraction that utilizes selective macrocyclic receptors can serve as a useful tool for removal of chemical wastes. Hemicucurbiturils are known to form inclusion complexes with suitably sized anions; however, their use in selective binding of non-charged species is still very limited. In this study, we found that cyclohexanohemicucurbit[8]uril encapsulates five- and six-membered sulfur- and oxygen-containing unsubstituted heterocycles, which is investigated by single-crystal X-ray diffraction, NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In this context, we have combined the binding properties of metalloporphyrins, which have widely been used for the realization of molecular receptors in chemical sensors with the facile preparation of enantiomerically pure form of cycHC[8] as chiral macrocyclic effectors. , Hemicucurbiturils can bind electron-rich species inside , the cavity and electron-deficient species outside their ring. , We exploit the latter property to promote the interaction with the metal ions coordinated to several porphyrins to realize chiral hybrid adducts in the solid state. In this way, we have designed solid-state sensors where a chiral block, cycHC, induces chirality in different metalloporphyrins, which in turn act as receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have combined the binding properties of metalloporphyrins, which have widely been used for the realization of molecular receptors in chemical sensors with the facile preparation of enantiomerically pure form of cycHC[8] as chiral macrocyclic effectors. , Hemicucurbiturils can bind electron-rich species inside , the cavity and electron-deficient species outside their ring. , We exploit the latter property to promote the interaction with the metal ions coordinated to several porphyrins to realize chiral hybrid adducts in the solid state. In this way, we have designed solid-state sensors where a chiral block, cycHC, induces chirality in different metalloporphyrins, which in turn act as receptors.…”
Section: Introductionmentioning
confidence: 99%
“…A family of cycHC[n]s consists of chiral and nonchiral (n = 6, 8, 12) members [37][38][39][40] and features, analogous to all single bridged cucurbiturils [41,42], binding anions inside the macrocycle cavity. Additionally, cycHC[n]s bind hydrogen bond donors and electron-rich organic molecules [43,44]. Upon complexation of chiral cycHC[n]s with achiral and CD silent zinc octaethylporphyrin (ZnOEP) and zinc tetraphenylporphyrin (ZnTPP) in CH 2 Cl 2 , an ICD signal is observed in the region of the porphyrin Soret band [36].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent organic pollutants that occur in different environmental matrices create a need for their sensing, removal and remediation. Cyclohexanochemicucurbit[n]urils (cycHC[n], n = 6 or 8) are chiral macrocyclic cavitands with a well-defined electron-deficient cavity suitable for the accommodation of various electron-rich guests [1][2][3]. The current work describes the application of cycHC[8] as a molecular container for the encapsulation of small neutral organic molecules, including environmental pollutants (mustard gas degradation products, haloalkanes) and biologically active compounds.…”
mentioning
confidence: 99%
“…Complexation studies in solution through 1H NMR and ITC revealed host-guest interactions between cycHC[8] and hydrophobic S-and O-containing neutral heterocycles, as well as small haloalkanes, in methanol and methanol-water media, resulting in stronger binding upon an increase in solvent polarity. Since the macrocycle is insoluble in water, it was further utilized for the selective capture of the neutral guests from aqueous solutions [3].…”
mentioning
confidence: 99%